Wage structure and unionization in the US construction sector - Cihan Bilginsoy (The University of Utah, Department of Economics, 2009)
This paper estimates the union effects on the wage gap and dispersion in two pooled samples of construction craftworkers (CPS 1983-88 and 2000-05) using decomposition analysis and kernel density estimation. It shows that despite the decline in the adjusted union wage gap declined over time, the unadjusted union wage premium remained high due to the divergence of returns to workforce characteristics in favor of union workers. This pattern was more marked in the basic trades in comparison with the mechanical trades. Unions also contributed to a wider wage dispersion because they created a union wage gap and this wage gap increased across the competitive wage distribution. Unions raised the wages of workers who were located in the middle of the wage density but did not have an effect on the lower wage workers.
Keywords: J3; J5; L7; 330; wage structure; unionization; construction; Bauwirtschaft; Gewerkschaftsmitgliedschaft; Lohnstruktur; USA